LOCAL WISDOM OF SUNAN AMPEL TOMB, SUNAN DRAJAT TOMB, AND BAJANG RATU TEMPLE - Putut Handoko; Rahadiyan Duwi Nugroho; Cahyaningsih Pujimahanani; Hariyono Hariyono; Kusuma Wijaya (Yayasan Literasi Sains Indonesia, 2026)
Local wisdom examines an essential aspect of cultural identity, social values, and community resilience, particularly within three heritage sites. This study aims to analyze the forms and functions of local wisdom embodied in three significant cultural sites in East Java: the tomb of Sunan Ampel, the tomb of Sunan Drajat, and Bajang Ratu Temple. Employing a qualitative descriptive method, data were collected through observation, documentation, and literature review to ensure systematic and valid interpretation. The findings reveal that each site reflects distinctive yet interconnected forms of local wisdom. The Sunan Ampel cemetery emphasizes moderation, spiritual devotion, and personal transformation, as seen in the figures of Sunan Ampel Lembu ,Peteng, Mbah Sholeh, and Mbah Bolong. Sunan Drajat site highlights social welfare, humanitarian values, and moral responsibility, particularly through the symbolic meanings of its stairways, which promote empathy, vigilance, perseverance, spiritual discipline, and charity. Meanwhile, Bajang Ratu Temple demonstrates a synthesis of Hindu-Buddhist philosophy and local wisdom through its architectural design, narrative reliefs, and symbolic ornaments, representing moral teachings, cosmic balance, spiritual protection, and transformation.